Nonlinear analysis of mm waves excitation by high–current REВ in dielectric resonator - Galaydych, K.V.; Lonin, Yu.F.; Ponomarev, A.G.; Prokopenko, Yu.V.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2012)
A nonlinear self-consistent theory of excitation of millimeter wave lengths electromagnetic fields by high current relativistic azimuthally-modulated electron beam in cylindrical resonator with a dielectric rod is constructed. For generation of high frequency waves is used an electron beam. Nonlinear numerical analysis is carried out.